Mattering and Perfectionism among Gen-Z: The Role of Personal Standards and Evaluative Concerns Perfectionism on Mattering - Zoe Lee; Kususanto Ditto Prihadi; Eva Nur Rachma (International Journal of Public Health Science (IJPHS), 2022)
Mattering is the sense that one matters to others, and it is one of the most significant protective factors against depression and anxiety. To date, most studies of mattering have established that it is contingent upon interpersonal factors, such as how one socializes with others and perceives how others value them; little did we study any internal psychological trait that might help in developing better mattering. In the light of that, this current study aims to investigate whether a personality disposition called perfectionism plays a significant role in predicting the sense of mattering. The role of two major elements of perfectionism, namely evaluative concern perfectionism (ECP) and personal standard perfectionism (PSP) was investigated. ECP was considered as the predictor due to the nature of its contingency upon one’s perception of others’ standard of acceptance, while PSP was included as a moderator because the level of personal standard might determine how ECP predicts the sense of mattering. Participants were purposively recruited to make sure that they were members of Generation-Z (Gen-Z). As many as 130 undergraduate students aged 18 to 24 years old were asked to respond to the subscales of the Frost Multidimensional Perfectionism Scale and the Interpersonal Mattering Scale through an online survey. The data was analyzed with a help of the software of PROCESS Macro for bootstrapping method with 95% confidence interval and 5000 samplings, and the results revealed that when PSP is at its highest levels, the link between ECP and mattering is no longer significant.